The use of non-prescription medicines during lactation: A qualitative study of community pharmacists' attitudes and perspectives - Sim, T.; Hattingh, H. Laetitia; Sherriff, Jill; Tee, L. (Elsevier, 2017)
© 2017 Elsevier Inc. Background: Community pharmacists play a significant role in the provision of non-prescription medicines. There is evidence that women self-medicate and use non-prescription medicines whilst breastfeeding. Studies have demonstrated that breastfeeding women are likely to seek advice from pharmacists, presenting a unique opportunity for pharmacists to provide on-going support of these women especially in relation to the appropriate use of non-prescription medicines. Objectives: This study aimed to explore community pharmacists' attitudes and perspectives towards the use of non-prescription medicines during breastfeeding. Methods: This exploratory study was conducted through semi-structured interviews with 30 community pharmacists in Western Australia, between July and September 2013. Transcribed data were analysed using descriptive and qualitative approaches. NVivo ® Version 10.0 was used to organise qualitative data and quotations to facilitate thematic analysis. Results: Four major themes emerged. Despite the positive attitudes and favourable perceived knowledge level, participants often found themselves in a dilemma when required to make clinical recommendations especially in situations where there was a therapeutic need for treatment but clear guidelines or evidence to suggest safety of the medicines or treatment in lactation was absent. Despite the popularity of complementary medicines, participants felt more confident in providing advice in relation to conventional over complementary medicines. Whilst medication safety is within the field of expertise of pharmacists, the absence of information and safety data was seen as a major challenge and barrier to enable pharmacists to confidently provide evidence-based recommendations. Conclusions: This study has enhanced our understanding of the attitudes and perspectives of community pharmacists towards the use of non-prescription, including complementary medicines, during breastfeeding. Future studies are warranted to confirm the safety of commonly used or requested medicines in breastfeeding. University training and continuing education for pharmacists should include the latest information available regarding the use of both conventional and complementary medicines throughout lactation.